Circumscription: Proust's The Captive and the Problem of Other Minds - Carol de Dobay Rifelj (Studies in 20th & 21st Century Literature, 1984)
Central to Proust's Remembrance as a whole and to The Captive in particular is Marcel's attempt to discover what other people think and feel. But, as reading the work in the light of modern analytic philosophy shows, his efforts are thwarted by the deceptions of others and by his own irreconcilable views. The other is radically inaccessible, yet the object of our search; the self is a stable entity, yet multiple, changing, and a fiction constituted by language; language is communication, yet the source of error. These are the problems which confront philosophy and literature when they try to come to terms with the otherness of others.
Keywords: Proust; Remembrance; The Captive; inaccessible; accessibility; inaccessibility; self; language; communication; error; philosophy; otherness; others